Assessment of Natural Radioactive Concentration Levels in the Oil Drilling Wells in Erbil Governorate Blocks - Ahmed I. Samad; Ali H. Ahmed; Saman K. Ezzulddin (Jordan Journal of Physics, 2025)
The activity concentrations of 226Ra, 232Th and 40K in the core samples obtained from Erbil oil blocks have been measured by using NaI(TI) gamma ray spectrometry. Radiological hazard indices were evaluated from the activity concentrations of these radionuclides in order to estimate health effects of the exposure of the public to radiation at the studied area. The calculated Radium equivalent activity (Raeq) varied from (33.48) to (321.13) Bq.kg-1 with a mean value of (127.50) Bq.kg-1. The values of annual gonadal equivalent doses (AGED) indicated 57.89% exceeding the limit of the maximum contamination level. The measured absorbed dose rate (D) values ranged from (16.17) to (140.43) nGy/ h, with a mean value of (56.95) nGy/ h in the oil field, which were 36.8 % higher than the international recommended value of 60 nGy/h [11]. Representative level index, Iγ, for all the samples varied from (0.25 to 2.23), with a mean value of (0.90). The external hazard index (Hex) varied from (0.09 to 0.87) with a mean value of (0.34) and the internal hazard index (Hin) ranged from (0.18 to 2.17), with a mean value of (0.91). The calculated annual effective dose equivalent values were %42 higher than the recommended value of (0.29). On the other hand, the values of ELCRin in all the samples were higher than the maximum contamination level of (0.29). The measured values of outdoor and indoor AEDE varied from (0.02 to 0.18) mSv/y and from (0.05 to 0.69) mSv/y, with the mean values of (0.07) and (0.28) mSv/y for outdoor and indoor effective doses respectively, which were all below the maximum contamination level of (1) mSv/y. Keywords: Radioactivity, Hazard indices, NaI(TI) detector, Oil field.